The duality of collaboration: inducements and opportunities in the formation of interfirm linkages - Ahuja, Gautam (Strategic Management Journal, 2000)
I argue that the linkage-formation propensity of firms is explained by simultaneously examining both inducement and opportunity factors. Drawing upon resource-based and social network theory literatures I identify three forms of accumulated capital—technical, commercial, and social—that can affect a firm’s inducements and opportunities to form linkages. Firms possessing these capital stocks enjoy advantages in linkages formation. However, firms lacking these accumulated resources can still form linkages if they generate a radical technological breakthrough. Thus, I identify paths to linkage formation for leading as well as peripheral firms. I test these arguments with longitudinal data on technical collaborative linkages in the global chemicals industry. Copyright © 2000 John Wiley & Sons, Ltd.